THE EFFECT OF PRINCIPALS’ TRANSFORMATIONAL LEADERSHIP STYLE ON TEACHER PERFORMANCE IN PUBLIC JUNIOR HIGH SCHOOLS IN THE LEMBAH GUMANTI SUBDISTRICT - Lira Rahmadani; Yulianto Santoso; Ermita Ermita; Widiawati Widiawati (STKIP Pesisir Selatan, 2026)
This study was motivated by issues related to teacher performance, namely low work initiative, limited proficiency in using educational technology, and suboptimal communication. One factor influencing these conditions is the principal’s transformational leadership style. This study aims to determine the level of teacher performance, the level of the principal’s transformational leadership style, and their relationship. The research method used was quantitative and correlational. The population consisted of 201 teachers. The sample comprised 140 teachers selected using the Cochran formula and proportionate stratified random sampling. Data were collected using a questionnaire with a Likert scale and analyzed using simple linear regression, t-tests, and the coefficient of determination with the aid of SPSS version 27. The results indicate that both teacher performance and the principal’s transformational leadership style fall into the high category, with a percentage of 83%. There is a positive and significant influence of the principal’s transformational leadership style on teacher performance, with a calculated t-value of 9.649 > the critical t-value of 1.977 and a significance level of 0.000 < 0.05. The coefficient of determination showed an R-squared value of 0.403, meaning that the principal’s transformational leadership style contributed 40.3% to teacher performance, while the remainder was influenced by other factors outside the scope of this study.